A SHA-512 Hardware Implementation Based on Block RAM Storage Structure - Yang, Mingyuan; Zhang, Yemeng; Yang, Bohan; Wang, Hanning; Yin, Shouyi; Wei, Shaojun; Liu, Leibo (2022 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW), 2022)
The Secure Hash Algorithms (SHAs) are essential building blocks of modern cryptographic systems. The imple-mentation dimensions of secure hash algorithms are explored for different application scenarios. Cloud servers may favor an implementation with considerable throughput, while a compact implementation with acceptable speed and sustainable power is crucial for the Internet of Things (IoT). In this paper, we present an implementation of SHA-512 for FPGA platform based on Block RAM (BRAM) storage structure. Three implementation techniques are proposed to facilitate the usage of BRAMs as replacements for Look-Up Tables (LUTs) and Flip-Flops (FFs) to achieve a balanced FPGA utilization. Compared to other FPGA implementations of SHA-512, our design has one of the smallest slice consumption while maintaining a moderate but sufficient throughput for cryptographic applications like the post-processing of true random number generators (TRNGs).